2007
DOI: 10.1016/j.freeradbiomed.2007.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenic effects of 8-hydroxy-dGTP in live mammalian cells

Abstract: The mutagenicity of an oxidized form of dGTP, 8-hydroxy-2'-deoxyguanosine 5'-triphosphate (8-OH-dGTP), was examined using COS-7 cells. 8-OH-dGTP and supF shuttle plasmid DNA were co-introduced by means of cationic liposomes, and the DNAs replicated in the cells were recovered and then transfected into Escherichia coli. These results constitute the first direct evidence to show that 8-OH-dGTP actually induces mutations in living mammalian cells. 8-OH-dGTP induced

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 57 publications
2
29
1
2
Order By: Relevance
“…Previously, we reported that A:T → C:G transversions were specifically induced by 8-oxo-dGTP in mammalian cells [48,51]. In this study, we examined the mutagenic potential of 8-oxo-dGTP in cells with knocked-down DNA glycosylases.…”
Section: Decrease In 8-oxo-dgtp-induced Mutations By Knock-down Of Mutyhmentioning
confidence: 99%
“…Previously, we reported that A:T → C:G transversions were specifically induced by 8-oxo-dGTP in mammalian cells [48,51]. In this study, we examined the mutagenic potential of 8-oxo-dGTP in cells with knocked-down DNA glycosylases.…”
Section: Decrease In 8-oxo-dgtp-induced Mutations By Knock-down Of Mutyhmentioning
confidence: 99%
“…Pursell et al demonstrated that the concentration of 8-OH-dGTP was 1-10% of that of unmodified dGTP in the mitochondrial nucleotide pool [18]. 8-OH-dGTP is mutagenic and specifically induced A:TC:G transversions in living bacterial and mammalian cells [19][20][21]. The A:TC:G mutations seem to be triggered by the incorporation of 8-OH-dGTP opposite A in template DNA, resulting in the formation of 8-OH-Gua:A base pairs, and the subsequent incorporation of dCTP opposite 8-OH-Gua during the next round of replication would cause the transversion [22].…”
Section: -Oh-gua Is Highly Mutagenic and Induces G:ct:a Transversiomentioning
confidence: 99%
“…8-OH-Gua was introduced into positions 122 and 96 of the sense strand of the supF gene for 8-OH-Gua:C and 8-OH-Gua:A, respectively. Position 96 was one of the 9 A:TC:G hot spots in the supF gene when 8-OH-dGTP was introduced [20,21]. Plasmid DNAs containing G:C and T:A at positions 122 and 96, respectively, were used as control plasmids.…”
Section: Design Of Plasmid Dnas Involving 8-oh-guamentioning
confidence: 99%
See 1 more Smart Citation
“…The mutagenicity of 8-OH-dGTP in mammalian cells was examined by the introduction of 8-OH-dGTP plus shuttle plasmid DNA containing the supF gene into simian COS-7 and human 293T cells [18,19]. The oxidized form of dGTP induced A:TC:G substitution mutations in mammalian cells, as in E. coli cells.…”
Section: Induced Mutations In Mammalian Cellsmentioning
confidence: 99%